KARAKTERISTIK PERMUKIMAN DAERAH KOTO DI KABUPATEN KUANTAN SINGINGI, PROVINSI RIAU - Yandri, Sepli; Sari, Suzanna Ratih; Sardjono, Agung Budi (Jurnal Arsitektur ARCADE, 2019)
Abstract: An area usually has an important area as the center of government activities. as found in every area in Kuantan Singingi Regency. Every region in Kuantan Singingi district has an area that functions as a customary area. the customary area is named as koto. Traditional Koto settlements are one of the traditional settlements in Kuantan Singingi that try to maintain culture amid the development of modernization. In the Koto area, there are buildings that function as customary buildings, namely in the form of the Koto mosque, balai, and Koto house building. These three buildings are a sign that this area is the center of traditional activities in a region. The purpose of this study was to find buildings that functioned as traditional activities and concluded the characteristics of settlements which became the identity of traditional settlements in Kuantan Singingi. The method of descriptive analysis is used as a method of delivering descriptions relating to the traditional settlement of the Koto area by analyzing traditional settlements in the Koto Benai and Koto Sentajo.Keyword: Traditional Settlement, Vernacular Architecture, Kuantan Singingi Traditional House, Koto House.Abstract: Suatu daerah memiliki sebuah kawasan yang penting sebagai pusat kegiatan pemerintahan. Begitu pula yang terdapat pada setiap kenegrian di Kabupaten Kuantan Singingi. Setiap kenegrian di Kuantan Singingi memiliki daerah yang berfungsi sebagai kawasan adat. Kawasan adat tersebut diberi nama dengan sebutan koto. Permukiman tradisional koto menjadi salah satu permukiman tradisional di Kuantan Singingi yang berusaha mempertahankan budaya ditengah perkembangan modernisasi. Pada daerah koto terdapat bangunan yang berfungsi sebagai bangunan adat yaitu berupa bangunan mesjid, bangunan balai adat, dan bangunan rumah adat. Ketiga bangunan ini menjadi pertanda bahwa daerah ini adalah sebagai pusat kegiatan adat istiadat dalam suatu nagori (negri).Â  Tujuan penelitian ini untuk menemukan bangunan yang berfungsi sebagai aktivitas adat dan menyimpulkan karakteristik permukiman yang menjadi identitas permukiman tradisional di Kuantan Singingi. Metode deskripsi analisis, di pakai sebagai cara penyampaian deskripsi mendalam terkait permukiman adat daerah koto dengan menganalisa permukiman tradisional pada daerah Koto Benai dan Koto Sentajo.Kata Kunci : Permukiman Tradisional, Arsitektur Vernakular, Rumah Adat Kuantan Singingi, Rumah koto.